Fine root dynamics and associated nutrient flux in Sal dominated forest ecosystems of Central Himalaya, India - Pandey, Rachita; Bargali, Surendra Singh; Bargali, Kiran; Karki, Himani; Kumar, Munesh; Sahoo, U. K. (Frontiers in Forests and Global Change, 2023)
The belowground systems of trees have a major role in forest functioning through absorption of water and nutrient cycling. This study deals with the fine root dynamics including fine root biomass, necromass, production, turnover and nutrient return in transitional Sal (Shorea robusta) dominated sub-tropical forest ecosystems of Central Himalaya, India. Four sites namely, Site-1 (Kaladhungi), Site-2 (Fatehpur), Site-3 (Ranibagh), Site-4 (Amritpur) were selected in Sal forest within an elevational range between 405 m and 580 m above sea level. The dominant and associated co-dominant species were selected from each site for the estimation of fine root dynamics by using sequential core and in-growth core methods. The results revealed that the fine root biomass, necromass and production were significantly (p < 0.05) affected by sites, seasons and soil properties. The fine root biomass and production decreased with increasing soil depth and also influenced by stand characteristics including tree density and tree basal area. The rainy season was most productive with maximum fine root biomass (507.37 kg ha-1 season -1) as well as fine root production (600.26 kg ha-1 season -1) in the dominant tree species Shorea robusta and in the associated co-dominant tree species Tectona grandis (330.48 kg ha-1 season -1 and 410.04 kg ha-1 season-1), while minimum in the winter season for G. velutinum tree species (126.72 kg ha-1 season -1and 195.59 kg ha-1 season -1). Annual fine root production was recorded between 148.73 and 572.78 kg ha-1 yr -1, while turnover rate varied from 1.37 to 4.45 yr-1 across the sites. The fine roots added carbon 154.38-564.20 kg ha-1 yr-1and 6.58-24.34 kg ha-1 yr-1nitrogen to the soil through annual flux. The study improves our understanding on fine root parameters under the influence of sites, soils and seasonal and spatial variation. The return of nutrients to the soil through fluxes from the roots illustrates the role of fine roots in carbon and nitrogen cycling of the forests and this potential can be harnessed to assess the long-term carbon and nitrogen pool estimations in forests and to plan and manage the forest ecosystems.